Wireless home monitoring and health care activity management through the Internet in patients with chronic diseases. - Tura, Andrea
A project was developed for the creation of an Internet-based network aimed at improved management of home care activities in brain-injured children. At the patient's side, a home care unit was provided, made of a portable medical device, and a table PC. Measured clinical data were blood oxygen saturation, heart rate, breath rate and quantity of movement. Thanks to device portability, the patient was free to move while measurements were taken. At prescribed time intervals, measured data were automatically transmitted to the table PC via Bluetooth. From the tablet PC, data were transmitted remotely to a Service Centre (via ADSL or GPRS) and made available for consultation by health care professional through the project Web portal. At the portal, other functionalities were also available, both for patients and families, and for professionals (such as weekly planning agenda, access to relevant information resources, communication tools). Information was delivered for the right participant through a workflow engine. A first trial involving nine patients was performed for two months. At the end, although some improvements were suggested, good acceptance was detected and 78% of patients and families claimed to be interested in further use of the platform.
Keywords: Portable medical device; Bluetooth; Web portal; Workflow; Brain-injured children